RAGE does not contribute to renal injury and damage upon ischemia/reperfusion-induced injury - Dessing, Mark C.; Nawroth, Peter Paul; Bierhaus, Angelika (Journal of innate immunity, 2012)
The receptor for advanced glycation end products (RAGE) mediates a variety of inflammatory responses in renal diseases, but its role in renal ischemia/reperfusion (I/R) injury is unknown. We showed that during renal I/R, RAGE ligands HMGB1 and S100B are expressed. However, RAGE deficiency does not affect renal injury and function upon I/R-induced injury.